The Assessment and Evaluation of Noneconomic Environments by American Firms: A Preliminary Report - Kobrin, Stephen J.; Basek, John; Blank, Stephen; Palombara, Joseph La (Journal of International Business Studies, 1980)
This paper reports preliminary results of a study of how relatively large U.S. international firms assess noneconomic environments, how the resulting evaluations are integrated into decision making or planning, and how the process affects managerial strategy. A mailed survey of 455 firms was followed up by personal interviews with approximately 113 managers in 37 firms selected via a stratified quota sample of respondents. Findings support a conclusion that assessment and evaluation of nonmarket environments is emerging as a new managerial function in relatively large international firms. Over half of the respondents indicated that they have a group or groups which have been assigned formal assessment responsibility; however, both the survey results and interview data suggest a number of problems with current practice. Assessments tends to be reactive rather than active; the most important sources of information about environments are internal to the firm; assessments are typically not conducted independently of an investment or planning proposal; and resulting evaluations serve as a context in which decisions are taken rather than as input to a decision-making process.